ANALISIS IMPLEMENTASI ADMINISTRASI SEKOLAH DI MAS AL HIJRAH KABUPATEN BUOL - Saprudin; Yusuf, Sofyan A.; Pattajani, Sutra Y. (STISIPOL Mujahidin Buol, 2025)
Administrative order and regularity are essential because they are a crucial component of the learning process. Some school administrations are deemed inadequate, resulting in a backlog of school records and archives, making it difficult to retrieve them when needed. This study aims to analyze the implementation of school administrative tasks using evaluation methods, which are methods used to assess an activity or program. Data collection techniques included questionnaires, observation, and documentation. The data were then analyzed qualitatively. The results indicate that the implementation of school administration in the areas of personnel administration, financial administration, infrastructure administration, public relations administration, archiving administration, and student administration is categorized as good. Overall, 67% of respondents answered that administrative services were good, 31% answered that they were quite good, and 2% answered that they were not good. This means that the implementation of school administrative work is generally good.